Analisis Engagement Media Sosial Melalui Pendekatan Berbasis Data Interaksi Pengguna untuk Meningkatkan Efektivitas Pemasaran Digital - Alfaini, Maziya Naila; Raharjo, Raden Johnny Hadi (BISNIS, 2026)
The advancement of digital technology has positioned social media as a critical instrument in modern marketing, including for service companies such as PT Naruna Karya Bersama. The company utilizes Instagram (@parentinganakusiadini_) as its primary digital marketing communication channel. This study aims to analyze the current social media engagement condition, identify influencing factors, and formulate improvement strategies through a data-driven descriptive approach with recommendatory outputs. A qualitative descriptive method was employed using four months of social media activity observation, documentation, and interviews with the management team. Data were analyzed through descriptive quantitative analysis (tabulation of ER by content format and posting time) and subsequently interpreted qualitatively through reduction, presentation, and conclusion drawing. Findings indicate that low engagement is driven by inconsistent content planning, suboptimal platform-specific strategy adaptation, limited active audience interaction, and a potentially inactive follower base. Strategic recommendations include interactive content optimization, upload timing adjustments based on temporal ER data, and enhanced two-way communication to strengthen the company's digital marketing effectiveness.